2015
DOI: 10.1002/anie.201409524
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electron Penetration through an Ultrathin Graphene Layer for Highly Efficient Catalysis of the Hydrogen Evolution Reaction

Abstract: Major challenges encountered when trying to replace precious-metal-based electrocatalysts of the hydrogen evolution reaction (HER) in acidic media are related to the low efficiency and stability of non-precious-metal compounds. Therefore, new concepts and strategies have to be devised to develop electrocatalysts that are based on earth-abundant materials. Herein, we report a hierarchical architecture that consists of ultrathin graphene shells (only 1-3 layers) that encapsulate a uniform CoNi nanoalloy to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
686
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,148 publications
(742 citation statements)
references
References 45 publications
33
686
0
1
Order By: Relevance
“…Several studies on CoNi alloys report performance of submicron size powder electrodes, 22 porous foams, 23 or even encapsulating CoNi nanoalloys in ultrathin layers of graphene. 24 Unlike other attempts to replace precious-metal-based electrocatalysts of HER, lowering efficiency and stability of such compounds, CoNi@C fabricated by Deng et al 24 are claimed to possess high performance. The optimized catalyst exhibits high stability and activity with an onset overpotential of almost zero versus the reversible hydrogen electrode (RHE) and an overpotential of only 142 mV at 10 mA cm À2 , which is quite close to that of commercial 40% Pt/C catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on CoNi alloys report performance of submicron size powder electrodes, 22 porous foams, 23 or even encapsulating CoNi nanoalloys in ultrathin layers of graphene. 24 Unlike other attempts to replace precious-metal-based electrocatalysts of HER, lowering efficiency and stability of such compounds, CoNi@C fabricated by Deng et al 24 are claimed to possess high performance. The optimized catalyst exhibits high stability and activity with an onset overpotential of almost zero versus the reversible hydrogen electrode (RHE) and an overpotential of only 142 mV at 10 mA cm À2 , which is quite close to that of commercial 40% Pt/C catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…1e), which agrees well with the (111) crystal plane of CoNi alloy. 17 TEM elemental mapping shows that N and C signals are uniformly distributed within carbon nanotubes, whereas Co and Ni signals are only detected at the black-contrast apical domains in the upper carbon nanotube sections. These findings suggest that nitrogen element is doped into the carbon nanotubes, and the metal NPs within the carbon nanotubes are comprised of Co and Ni elements.…”
Section: Resultsmentioning
confidence: 96%
“…We hypothesize that the alloyed CoNi NPs 8 within the CoNi@NCNT/NF may have synergistic effects that further improve nitrogen dopant catalytic activity. 17 To better understand the effect of apical dominance for improving the catalytic activity of NCNT arrays, we proposed a mechanistic model to illustrate the electrochemical process on CoNi@NCNT/NF and NCNT/NF electrodes, respectively. A typical schematic diagram of the CoNi@NCNT/NF electrode is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[64,81] Generally speaking, metal NPs embedded in carbon shells cannot only increase electron transport, but also change the local work function for tuning the adsorption of intermediates. [64,82] For example, the pioneering work reported by Deng et al indicated that CoNi NPs coated by ultrathin graphene shells (carbon layers < 3) enabled enhanced electron penetration from the metal cores to the carbon shells, thereby modulating the electron density and the electronic structure of the graphene surface. [82] This effect further tuned free energy for the adsorption of intermediates to enhance catalytic activity.…”
Section: Transition Metal Incorporationmentioning
confidence: 99%
“…[64,82] For example, the pioneering work reported by Deng et al indicated that CoNi NPs coated by ultrathin graphene shells (carbon layers < 3) enabled enhanced electron penetration from the metal cores to the carbon shells, thereby modulating the electron density and the electronic structure of the graphene surface. [82] This effect further tuned free energy for the adsorption of intermediates to enhance catalytic activity. At the same time, their study demonstrated the synergistic effect between N dopants and enclosed metal clusters for further enhanced activity.…”
Section: Transition Metal Incorporationmentioning
confidence: 99%